Implementasi Sistem Monitoring Detak Jantung dan Suhu Tubuh Manusia Secara Wireless - Muhlis Agung Saputro; Edita Rosana Widasari; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Heartbeat and body temperature are vital signs that routinely checked by the hospital to determine the clinical signs are used to confirm the diagnosis of a disease. In the process, heartbeat and body temperature checking in some hospitals still use manual system where a nurse had to come to the patient room to check and record heartbeat and body temperature of the patient. This system is less effective because it takes a lot of time. In this research has been created a monitoring system of the heartbeat and body temperature wirelessly. The system uses pulse sensors to detect the heartbeat, LM35 to detect body temperature, for data processing using Arduino nano and utilize NRF24L01 as wireless data transmission media. This system detects heartbeat and body temperature in real time. The processed data is then displayed on an application. The information provided on the application include heartbeats per minute, body temperature, and indicators of the condition of the heartbeat and body temperature of the patient. The application also have a features that can store heartbeat and body temperature at a certain time. Based on the test results, the success rate of the system in detecting heartbeats is 97.17%. While success rate of the system in detecting body temperature is 99.28%. For data transmission, the system can perform data transmission smoothly at a maximum distance of 15 meters to the barrier. For storage in the database, the system can store data as expected.